Acrolectal English for tertiary students: individualised metaphonological awareness instruction - Bromeley Philip,; John Francis Noyan, (Penerbit Universiti Kebangsaan Malaysia, 2018)
This paper explores the process of implementing the Individualised Metaphonological Awareness Instruction (IMAI) for the teaching and learning of acrolectal English in terms of the phonological aspect: selected suprasegmental features of English sound, namely, the schwa and catenation or linking features. For instance, not producing the neutral schwa vowel sound is in part what gives those whose second language is English an accent or pronunciation that is different from those whose first language is English. Producing or not producing schwa vowel sounds affects the quality of one’s pronunciation and how natural one sounds when speaking English. If the sophisticated learners aspire to approximate the RP model in their enunciation, schwa and catenation are deemed very important. The study assesses the instruction model in terms of its facilitative effects in assisting the teacher as well as in assisting the student to learn selected aspects of suprasegmental features of English sounds via scaffolding process. It is a qualitative case study which involves five (5) participant undergraduates at a public university in Sarawak. Only qualitative data involving one participant were reported and discussed in this paper. It was found that firstly the I-MAI model did assist both the teacher and the student in coaching and learning pronunciation respectively. The process of micro-scaffolding yielded varied scaffolding features/characteristics that explain the interactive dynamics occurring within the individualised instructional process itself. The I-MAI was also found to be positive and facilitative in enhancing the student’s metaphonological awareness of the suprasegmental features of English sounds.